Developing a self-determination motivation scale for English learners with Chinese background - Chiang, Juiching (Frontiers in Education, 2024)
“Interest” is one of the most important factors that trigger English learning behavior, and self-determination theory believes that “interest” and “value” are important factors associated with target behavior. Therefore, the purpose of this study is to construct and establish a “Self-Determination Motivation Scale of English Learners” based on the core concept of self-determination theory, which encompasses the three innate needs. There were 169 participants, all university students from various majors with Chinese backgrounds, who were taking English classes at a university. The research tool is extracted from the Learning Climate Questionnaire (LCQ) (six questions on autonomy), perceived competence for learning (PCS) (four questions on competence), and basic psychological needs (BPN) in general (eight questions on relatedness) and developed an 18-item questionnaire. The data were obtained from the existing three different self-determination questionnaires and analyzed using confirmatory factor analysis (CFA). The results show that after CFA, 15 items of the scale, which were extracted from the existing three different self-made questionnaires, were maintained, and the removed three items are all reverse items. The reliability of the developed 15-item scale is 0.95. The conclusion is that the developed 15-item scale is more suitable for university English learners with a Chinese background, although the existing three different self-determination questionnaires are still valid and reliable. Three suggestions for future research include adding expert validity for item review, adjusting the number of reverse items, and having more participants to master the scale. The implications, limitations, and future research plans are presented in this paper.